Return to work for cancer survivors: Importance and challenges - Kınacı Gümüşçubuk, Yağmur; Çalık Başaran, Nursel (Acta Medica, 2024)
The loss of gainful employment can lead to a diminished quality of life, reduced self-esteem, and financial difficulties for cancer survivors. Understanding the factors influencing their ability to re-enter the workforce is crucial. Providing workplace accommodations, reducing workloads, and fostering support from employers and colleagues can incentivize cancer survivors to return to work. Physicians also play a pivotal role in aiding patients through the return-to-work process, thereby enhancing their overall quality of life. Early evaluation and access to social support systems are essential for cancer survivors. In this comprehensive review, we examine the process of cancer survivors returning to work, the associated factors, and the primary challenges, drawing upon current research.